Infections in British clinical laboratories, 1988-1989. - Grist, N R (1991)
During 1988-89 this continuing survey showed 18 infections in the staff of laboratories reporting from 166 centres, representing 21,756 person-years of exposure. Shigella and other bowel infections (one caused by S typhi) predominated, affecting 11 microbiology medical laboratory scientific officers. Three shigella infections originated from quality control samples. Pulmonary tuberculosis affected four workers, including two mortuary technicians, but without detected occupational exposure to Mycobacterium tuberculosis. Other infections included one caused by Brucella melitensis. Hepatitis was not reported. The sustained low level of hepatitis is encouraging and suggests a low risk to staff of bloodborne infections such as human immunodeficiency virus.